(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses the ideological and artistic features of Abdulla Qahhor’s story "Muhabbat" (Love), which is permeated with the theme of love, the analysis of its artistic images, and its educational significance for humanity.